Sertraline has in vitro activity against both mature and forming biofilms of different Candida species. Issue 2 (9th February 2023) - Rodrigues, Daniel Sampaio; Cabral, Vitória Pessoa de Farias; Barbosa, Amanda Dias; Sá, Lívia Gurgel do Amaral Valente; Moreira, Lara Elloyse Almeida; de Andrade Neto, João Batista; da Silva, Cecília Rocha; de Moraes, Manoel Odorico; Silva, Jacilene; Marinho, Emmanuel Silva; dos Santos, Helcio Silva; da Costa, Érica Rayanne Mota; et al.
Abstract : Candida spp. infections are a serious health problem, especially in patients with risk factors. The acquisition of resistance, often associated with biofilm production, makes treatment more difficult due to the reduced effectiveness of available antifungals. Drug repurposing is a good alternative for the treatment of infections by Candida spp. biofilms. The present study evaluated the in vitro antibiofilm activity of sertraline in reducing the cell viability of forming and matured biofilms, in addition to elucidating whether effective concentrations are safe. Sertraline reduced biofilm cell viability by more than 80 % for all Candida species tested, acting at low and safe concentrations, both on mature biofilm and in preventing its formation, even the one with highest virulence. Its preventive mechanism seemed to be related to binding with ALS3. These data indicate that sertraline is a promising drug with anticandidal biofilm potential in safe doses. However, further studies are needed to elucidate the antibiofilm mechanism and possible application of pharmaceutical forms.